Pneumocystis Pneumonia in Non-HIV Pregnant Women Receiving Chemotherapy for Malignant Lymphoma: Two Case Reports - Yuki Fukutani; Yoshitsugu Chigusa; Eiji Kondoh; Kaoru Kawasaki; Shingo Io; Noriomi Matsumura (Hindawi Limited, 2017)
Pneumocystis pneumonia (PCP) is a life-threatening opportunistic infection that sometimes occurs in immunocompromised patients with human immunodeficiency virus (HIV). Here, we report two extremely rare cases of PCP in non-HIV pregnant women who underwent chemotherapy for malignant lymphoma. Case  1 is a 34-year-old primigravida who was diagnosed with Hodgkin's lymphoma. She received ABVD chemotherapy and developed PCP at 37 weeks of gestation. After the onset of PCP, emergent cesarean section was performed due to a nonreassuring fetal status. Case  2 is a 31-year-old multigravida with diffuse large B-cell lymphoma who was administered R-CHOP chemotherapy. At 34 weeks of gestation, she complained of dyspnea and developed PCP. She delivered her baby vaginally immediately after the onset of symptoms. Both patients were treated with sulfamethoxazole-trimethoprim (ST) and recovered shortly thereafter. The babies' courses were also uneventful. PCP remains a serious cause of death, especially in non-HIV patients, and, therefore, appropriate prophylaxis and a prompt diagnosis are imperative.